Do geocentrismo à gravitação universal: proposta e implementação de uma sequência didática para o ensino médio - Simon, Rodrigo de Almeida (2016)
This work is formed by the development and implementation of an Educational Product, which by means of a didactic sequence (DS), aimed to address geocentrism, heliocentrism and universal gravitation topics in a less classical approach, bringing diversified methodologies and didactic resources. In addition, we aimed to benefit the learning of students engaged in the use of the DS “Solar System Movements” by the teacher-researcher, as well as by other professors who, someway, use the activities proposed in this Educational Product in their classes. In this term paper, we presented an introduction to the developed study and an accurate theoretical exposition on the development of Geocentric and Heliocentric models up to the arrival of Newton´s Universal Gravitation; we discussed about theoretical-methodological basis considered in DS activities planning, which are mainly based on the didactic drawings principles described by Méheut and Psillos: Epistemological principles (applying History of Sciences (HS) in teaching); cognitive psychology principles (learning from prior knowledge and as an evolution of mental models); didactic principles (learning by modelling, the HS application in teaching and pedagogical use of Information and Communication Technologies (ICT)) and sociocultural principles (an interactive and joint work between teachers and students and pedagogical use of ICT). We also presented context, a report on the implementation of the Educational Product as part of an elective subject of Full-time High School and considerations on the entire progress of this Master thesis, as well as the professor, students’ and support materials for the use of DS.